Understanding the fast crystallization kinetics of In–Sb–Te by using ultrafast calorimetry. Issue 2 (13th December 2017) - Mu, Sen; Chen, Yimin; Pan, Hongbo; Wang, Guoxiang; Wang, Junqiang; Wang, Rongping; Shen, Xiang; Dai, Shixun; Xu, Tiefeng; Nie, Qiuhua
Abstract : The crystal growth rates of supercooled liquids In–Sb–Te can be well characterized by ultrafast DSC, and it benefits to the optimization for phase-change materials. Abstract : Obtaining information about crystallization kinetics is crucial to understand the transformation speed of phase-change materials and select materials for phase-change memory. In the current work, we first investigated the temperature dependence of the resistance of undoped and In-doped Sb4 Te films and found that the crystallization temperature ( T p ) and 10-year data retention of Sb4 Te increased significantly when it was doped with In. We further employed ultrafast differential scanning calorimetry to explore the crystallization kinetics of In-doped Sb4 Te with various compositions, and found In20 (Sb4 Te)80 to have has the fastest crystallization rate (∼7.1 m s −1 at 726.2 K). The In20 (Sb4 Te)80 film exhibited a high T p (∼503 K), better data retention ability (∼418.7 K for 10 years), and ultrafast crystallization with strong non-Arrhenius behavior. These results indicated In20 (Sb4 Te)80 to be a promising candidate for use in applications of phase change materials.